Spatial Patterns of Urban Shrinkage in Depopulating Municipalities in South Korea - Kang, Min-Kyeong; Park, Han-Na; Song, Jaemin (Journal of Korea Planning Association, 2025)
Population decline serves as both a cause and a consequence of urban shrinkage, increasing local financial burdens and undermining urban sustainability. Analyzing how population decline manifests and evolves spatially within cities is crucial to effectively implementing shrinking smart strategies. However, research that comprehensively analyzes internal spatial change patterns for depopulating cities is scarce. Against this backdrop, the study aims to identify the spatial patterns of urban shrinkage dynamics within depopulating municipalities in South Korea by quantifying spatial changes in urban and non-urban areas within each municipality, applying multi-temporal clustering to identify distinct shrinkage patterns, and finally analyzing the demographic, economic, and physical characteristics of each pattern. Our analysis reveals six distinct patterns of spatial shrinkage: Urban-Centralization and Urban-Led and Rural-Led Shrinkage, each with strong and moderate variations. These patterns demonstrate considerable variations in demographic, economic, and built environment characteristics. The findings offer a valuable basis for spatial planning and policy development aimed at managing urban shrinkage in a smarter way. KCI Citation Count: 0